2018
DOI: 10.1039/c7nr07300c
|View full text |Cite
|
Sign up to set email alerts
|

Low-force spectroscopy on graphene membranes by scanning tunneling microscopy

Abstract: Two-dimensional atomically flat sheets with a high mechanical flexibility are very attractive as ultrathin membranes but are also inherently challenging for microscopic investigations. We report on a method using Scanning Tunneling Microscopy (STM) under ultra-high vacuum conditions for non-indenting low-force spectroscopy on micrometer-sized freestanding graphene membranes. The method is based on applying quasi-static voltage ramps with active feedback at low tunneling currents and ultimately relies on the at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Many studies [23][24][25][26] experimentally characterizing Y obtain it by measuring E 2D , then back-calculating Y using equation (1). One group [27] experimentally measured D of multi-layered graphene (  L 8 c ), and found that it obeys equation (2), when Y is obtained as above.…”
Section: Computational Techniques: Ce Modelmentioning
confidence: 99%
“…Many studies [23][24][25][26] experimentally characterizing Y obtain it by measuring E 2D , then back-calculating Y using equation (1). One group [27] experimentally measured D of multi-layered graphene (  L 8 c ), and found that it obeys equation (2), when Y is obtained as above.…”
Section: Computational Techniques: Ce Modelmentioning
confidence: 99%
“…16 For Y, a significant amount of variation is present among literature reports. Y has been characterized by a number of methods; 15,[20][21][22][23][24] of these, methods that use atomic force microscopy to deform a region of freestanding graphene most closely resemble the geometry and loading in the present work, pointing to Y ∼1 TPa. 15,21,22 One of these studies showed that Y increases and then decreases as a function of defect density in graphene.…”
Section: U-termmentioning
confidence: 99%
“…AFM indentation measurements record values of k which reduce away from the edge of the void towards a minimum when suspended graphene is furthest from boundary clamping [31]. Our method lifts the graphene away from the surface and if the graphene-substrate forces which create the boundary clamping were reduced, we may measure lower values of k. If after deposition there is slack in the graphene layers, this too would reduce the apparent stiffness [8].…”
Section: Voltage-dependent Manipulationmentioning
confidence: 99%
“…Scanning tunneling microscopy (STM) is an ideal tool to both measure and manipulate graphene and other 2D materials by using the interaction of the probe to pull and push the graphene layers, simultaneously loading and measuring the electronic response [5][6][7]. As well as inducing and stretching ripples normal to the graphene plane, STM can also be used to perform stress-strain measurements on graphene, offering greater insights into its behavior when used in flexible electronics [8,9].…”
Section: Introductionmentioning
confidence: 99%